The Influence of Taxpayer Knowledge and Tax Awareness on Compliance Must Tax for Perpetrator Msmes in East Kara-wang District, Karawang Regency - Desi Natalia Malau; Lilis Lasmini; Ade Trisyanto (International Journal of Economics and Management Research, 2024)
This study aims to determine, analyze, and explain the influence of taxpayer knowledge and taxpayer awareness on taxpayer compliance among MSME actors in Karawang Regency. Tax compliance is an important aspect in ensuring the effectiveness of the tax system and the achievement of national revenue targets, especially given the significant contribution of MSMEs to Indonesia’s economy. A quantitative research approach was employed, with a sample size of 150 respondents selected from registered MSME taxpayers. Data were collected through questionnaires and subsequently analyzed using multiple linear regression techniques. Prior to hypothesis testing, validity and reliability tests were conducted to ensure the quality of the research instrument. The results of the study revealed that taxpayer knowledge did not have a positive but showed a statistically significant influence on taxpayer compliance. This suggests that knowledge alone is not sufficient to ensure compliance unless it is accompanied by awareness and willingness to comply. Conversely, taxpayer awareness demonstrated a positive and significant influence on compliance, highlighting the crucial role of intrinsic motivation and understanding of the importance of taxes for national development. Furthermore, the results also showed that taxpayer knowledge and taxpayer awareness together have a simultaneous effect on taxpayer compliance. These findings indicate that efforts to increase tax compliance should not only focus on disseminating knowledge but also on cultivating taxpayer awareness through education, counseling, and effective communication strategies. Such initiatives are expected to foster a culture of voluntary compliance among MSME actors, ultimately supporting sustainable tax revenue.